(untitled) (Revista LIDER, 2020)
Tourism as an economic and social phenomenon constantly evolve, because of high market competition or the change that suffers touristic practices related to the search of new products which satisfies this demand, which also characterize new forms of culture commodification and the effects of territorial appropriation (Cammarata, 2006). We start from the premise that all touristic activity belong to a geographical space, and build territories and territorialities, for social Actors that present different strategic links between them, basing on relational flows and put it in to a more like an operational interpersonal framework, rather than an institutional framework.